Peran linguistik Forensik dalam Mengidentifikasi Pesan Anonim - Usman Pakaya (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The widespread circulation of hoaxes and hate speech on social media has become one of the major challenges in the digital era. Provocative content, such as the Fufufafa case, demonstrates how language can be used as a tool to manipulate public opinion and trigger social conflict. This study employs a descriptive qualitative approach by analyzing user posts and comments containing hoaxes and hate speech. Data were collected through screenshot documentation, categorized, and analyzed within a forensic linguistics framework, focusing on lexical, pragmatic, and rhetorical aspects. The findings reveal that hoaxes are characterized by excessive generalizations, pseudo-factual claims, and hyperbolic diction; whereas hate speech is marked by negative labeling, stereotyping, and provocative diction targeting specific group identities. These results highlight the potential of forensic linguistics as a significant instrument in detecting and preventing the spread of harmful content in digital spaces. The study is expected to contribute academically to forensic linguistics research and provide practical benefits in enhancing society’s digital literacy.